FA04.04: IMPORTANT STEPS AND FIRST RESULTS OF FULLY ROBOTIC IVOR-LEWIS ESOPHAGEAL RESECTION (RAMIE4) FOR ESOPHAGEAL AND ESOPHAGOGASTRIC JUNCTION CANCER. (14th September 2018) - Grimminger, Peter; Hadzijusufovic, Edin; Babic, Benjamin; Matthias Corvinus, Florian; Lang, Hauke
Abstract: Background: Robotic-assisted surgery is increasing, especially in general tumor surgery. Minimal-invasive esophagectomy (MIE) is commonly the standard operation procedure in high-volume centers. Also the fully robotic minimally invasive esophagectomy using 4 robotic arms in the abdomen and thorax (RAMIE4) is performed more frequent. The advantages of RAMIE4 as well as advantages and disadvantages of special steps in the procedure and reconstruction are not clear so far and are under comparison with other MIE techniques. Methods: Form January 2017 until March 2018 we prospectively collect the first 50 fully robotic RAMIE4 cases performed by one specialized surgeon and additionally the 50 MIE cases performed by the same surgeon between 2016 and 2017. Results: At the meeting we will present our RAMIE4 results of the first 50 cases operated by one specialized surgeon and compare those results with the 50 MIE cases of the same surgeon. Additionally essential steps of the RAMIE4 procedure will be presented. Conclusion: In our opinion RAMIE4 is feasible and offers great potential, especially for lymph node dissection, surgical precision, future potential, teaching and advanced ergonomics. The overall advantages have to be proven in randomized trials by specialized surgeons in MIE and RAMIE. Disclosure: All authors have declared no conflicts of interest.